Evaluation of dentin hypersensitivity treatment with glass ionomer cements: A randomized clinical trial - Marina de Matos MADRUGA (Brazilian Oral Research)
Abstract A randomized, double-blind, split-mouth clinical trial was performed compared the desensitizing efficacy of the resin-modified glass ionomer cement (GIC) ClinproTM XT (3M ESPE, Minnesota, USA) and the conventional GIC Vidrion R (SS White, Gloucester, UK) in a 6-month follow-up. Subjects were required to have at least two teeth with dentin hypersensitivity. Teeth were divided at random into 2 groups, one group received Clinpro XT and the other conventional GIC Vidrion R. Treatments were assessed by tactile and air blast tests using Visual Analogue Scale (VAS) at baseline, after 20 minutes, and at 7, 15, 21, 30, 90 and 180 days post-treatment. Twenty subjects (152 teeth) were included. Both tests (tactile and air blast) showed a significant reduction of dentin hypersensitivity immediately after the application of Vidrion R and Clinpro XT (20 min). VAS scores obtained along the 6-month follow-up were statistically lower when compared to initial rates (p < 0.05). Both GIC were able to reduce dentin hypersensitivity up to 6-month post-treatment period without statistically significant differences among them (p > 0.05). Both cements provided satisfactory results in long-term dental sensitivity reduction.